Latino education : an agenda for community action research - Pedraza, Pedro, 1946-; Rivera, Melissa, 1971- (Lawrence Erlbaum Associates, 2005)
This volume represents the work of the National Latino/a Education Research Agenda Project (NLERAP) It conceptualizes and illustrates the theoretical framework for the NLERAP agenda and its projects.